If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 88 + -3x = 2x + 23 Reorder the terms: 88 + -3x = 23 + 2x Solving 88 + -3x = 23 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 88 + -3x + -2x = 23 + 2x + -2x Combine like terms: -3x + -2x = -5x 88 + -5x = 23 + 2x + -2x Combine like terms: 2x + -2x = 0 88 + -5x = 23 + 0 88 + -5x = 23 Add '-88' to each side of the equation. 88 + -88 + -5x = 23 + -88 Combine like terms: 88 + -88 = 0 0 + -5x = 23 + -88 -5x = 23 + -88 Combine like terms: 23 + -88 = -65 -5x = -65 Divide each side by '-5'. x = 13 Simplifying x = 13
| 3p+2q=18 | | 4x+9=-13-7x | | y-(-7)=6(x-(-4)) | | 7-10x=23-24x | | y-(-7)=-6(x-(-7)) | | 10x+18=5x+128 | | 2x-3y+4=0 | | 12x-5y=0 | | 10x+8=5x+128 | | 89-2x=3x+24 | | 160-7x=20x+19 | | 5x+6=-84-10x | | y=3(5)+23 | | 4x+31=12x-49 | | 7y-12=9 | | 4r+6=22 | | e-15=16 | | 6t=42 | | w-9=5 | | 11x+12=6x+102 | | h+7=15 | | 105-2x=25x+18 | | 12-9x=67-44x | | (n+4)x*4=48 | | 94-2x=43x-19 | | 126-5x=5x+6 | | 6a-6=42 | | 125-3x=5x+21 | | 237-3x=42x+22 | | 3n=12 | | 3x+2=18-5x | | x+8=3+2x |